(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Monkeypox (Mpox) is a zoonotic viral disease that has re-emerged as a global health concern since 2022. In countries with limited vaccine access, non-pharmaceutical interventions such as quarantine and environmental sanitation remain the primary control strategies. However, existing models rarely integrate both measures within a single analytical framework. This study develops and analyzes a deterministic SEIQR-C model that incorporates quarantine protocols and surface contamination to examine the transmission dynamics of monkeypox. The model divides the human population into susceptible, exposed, infectious, quarantined, and recovered compartments, alongside a contaminated-surface component. Using the next generation matrix approach, the basic reproduction number (R0) is derived, accounting for both direct and indirect transmis- sion. Analytical results show that the disease-free equilibrium is locally and globally asymptotically stable when R0 < 1, and that an endemic equilibrium exists when R0 > 1. Numerical simulations confirm that increasing quarantine efficiency and cleaning or decay rates significantly reduce infection persistence, underscoring their vital roles in controlling monkeypox outbreaks in low-resource settings.